ESTIGMA, INDIVIDUALISMO Y ORGANIZACIÓN. MICROPOLÍTICA DE LOS VÍNCULOS ENTRE MUJERES QUE HACEN COMERCIO SEXUAL EN ARGENTINA - Morcillo Pérez, Santiago (Universidad de Costa Rica, 2019)
This article addresses the links between women who perform commercial sex, traversed by both solidarity and the competitiveness of the sexual market. Based on in-depth interviews conducted in three cities of Argentina, the analysis ranges from inter-individual relations to broader ones within the framework of political organizations. The links between subaltern and stigmatized women are stressed between recognizing themselves as partners and equals in a “we” or (re) marking a hierarchical difference between the self and the “others”.